Stage IB Endometrioid Type Endometrial Cancer: The Role of Lymphadenectomy and Adjuvant Radiation Therapy - Osman Turkmen; Tolga Tasci; Derman Basaran; Gunsu Comert Kimyon; Alper Karalök; Isin Ureyen; Taner Turan (Medical Network, 2018)
Objective: Both performances of lymphadenectomy and benefit of adding adjuvant radiotherapy are controversial for patients with International Federation of Gynecology and Obstetrics stage IB endometrioid type endometrial cancer. We aimed to identify the role of lymphadenectomy and adjuvant radiation therapy as well as clinicopathological prognostic factors for this group of patients. Study Design: Records of all patients (n=132) with stage IB endometrioid endometrial cancer who were referred to or treated in our institution between Jan 1992 and Dec 2013 were retrospectively reviewed. Cox Proportional Hazard Regression Analysis was used to determine the effects of lymphadenectomy and adjuvant radiation as well as other clinicopathological factors on disease free survival and overall survival. Results: Mean age was 59.9 years (range, 45-82). Lymphadenectomy didn't perform in 36 (27.3%) patients and 23 (17.4%) patients did not have any kind of adjuvant treatment. Mean lymph node count was 18.8 (range, 3-67). Federation of Gynecology and Obstetrics grade, lymphovascular space invasion, lymphadenectomy, receiving adjuvant treatment and type of received adjuvant therapy were not associated with disease free survival and overall survival for the entire cohort. In a subgroup of patients with grade1&2 tumor, 5-year disease free survival rates were 80% and 50% (p=0.4), respectively and overall survival rates were 94.8% and 93.8% (p=0.2), respectively for patients who had or didn't have adjuvant radiotherapy. While performance of lymphadenectomy was not significantly associated with disease free survival in this subgroup (p=0.56), this association was statistically significant for overall survival (97.9% vs. 86.4%, p=0.04) Conclusion: Benefit of adjuvant radiotherapy in regard to prevention of recurrence needs to be confirmed by further studies. Lymphadenectomy had a survival benefit for patients with myometrial invasion greater than a half of myometrial thickness.